The Influence of Career Development and Work Potential on Employee Performance at the Public Housing and Settlement and Land Office (Perkim) of Lahat Regency - Shintya Ariani; Hestin Hestin; Rudi Eduar (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how career development and work potential partially and simultaneously influence employee performance at the Lahat Regency Public Housing, Settlement and Land Affairs Office (PERKIM). The sample size for this study was 50 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation . The results showed a significant relationship between career development and employee performance at the Lahat Regency Public Housing, Settlement and Land Affairs Office (PERKIM). The F-test indicated that career development and work potential simultaneously influenced employee performance at the Lahat Regency Public Housing, Settlement and Land Affairs Office (PERKIM).